Geneva rhetoric, national reality : the political economy of introducing plant breeders' rights in Kenya - Rangnekar, Dwijen (New Political Economy, 2013)
The article is about implementing obligations under Article 27.3(b) of the Agreement on Trade Related Aspects of Intellectual Property (TRIPS). However, concerned with the fragmentation of international law in a globalised world, the article uses Kenya as a case study to interrogate the apparent choice and latitude in Article 27.3(b). At the TRIPS Council, Kenya has sought to locate Article 27.3(b) within a wider frame by adroitly norm-borrowing, and it canvassed for integrating norms and principles from other multilateral agreements into TRIPS. Yet, when introducing plant breeders' rights into domestic law, Kenya fails to either explore the apparent latitude or deliver on its rhetoric in Geneva. I explain this decoupling between Geneva rhetoric (ritual) and domestic law (behaviour) as another symptom of what Steinberg [(2002), ‘In the Shadow of Law or Power? Consensus-Based Bargaining and Outcomes in the GATT/WTO’, International Organization, 56 (2), pp. 339–74)] characterises as ‘organised hypocrisy’ of the World Trade Organisation. In demonstrating that fragmentation in global legal architecture may not automatically emerge in domestic law, the article draws out the significance of attending to a domestic political economy of law-making.